2017 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--29133
|View full text |Cite
|
Sign up to set email alerts
|

WIP: Using a teamwork model to manage large teams in a large lecture

Abstract: Lilianny Virguez is a Ph.D. candidate in Engineering Education at Virginia Tech. She holds a master's degree in Management Systems Engineering. She has work experience in engineering and has taught engineering courses at the first-year level.Her research interests include motivation to succeed in engineering with a focus on first-year students. Ing. omar perez

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 3 publications
(4 reference statements)
0
8
1
Order By: Relevance
“…of pedagogies promoting these skills has been slow [45]. Studies examining the barriers to the adoption of such pedagogical activities concluded that instructors had concerns about devoting class time for interactive activities might cause loss of content coverage [41].…”
mentioning
confidence: 99%
“…of pedagogies promoting these skills has been slow [45]. Studies examining the barriers to the adoption of such pedagogical activities concluded that instructors had concerns about devoting class time for interactive activities might cause loss of content coverage [41].…”
mentioning
confidence: 99%
“…Lack of coordination, effective communication and conflicts were the major issues faced among the team members. However, these are challenges faced by students when working in small teams as well [11,13]. During the course, when these challenges were highlighted, engineering education researchers and instructors were involved in providing constructive feedback to the team members in order to overcome the challenges.…”
Section: Discussionmentioning
confidence: 99%
“…The teamwork training was designed by a group of Engineering Education researchers in an engineering design course at a research university in Australia [11]. The training was developed using Adams et al [13] teamwork framework as a reference.…”
Section: Teamwork Frameworkmentioning
confidence: 99%
See 2 more Smart Citations